Evaluation of right ventricular function with multidetector computed tomography: comparison with magnetic resonance imaging and analysis of inter- and intraobserver variability. - Müller M; Teige F; Schnapauff D; Hamm B; Dewey M; Müller, Mira; Teige, Florian; Schnapauff, Dirk; Hamm, Bernd; Dewey, Marc (European Radiology, 2009)
This study was performed to prospectively compare multidetector computed tomography (MDCT) with 16 simultaneous sections and magnetic resonance imaging (MRI) for the assessment of global right ventricular function in 50 patients. MDCT using a semiautomatic analysis tool showed good correlation with MRI for end-diastolic volume (EDV, r=0.83, p<0.001), end-systolic volume (ESV, r=0.86, p<0.001) and stroke volume (SV, r=0.74, p<0.001), but only a moderate correlation for the ejection fraction (EF, r=0.67, p<0.001). Bland Altman analysis revealed a slight, but insignificant overestimation of EDV (4.0 ml, p=0.08) and ESV (2.4 ml, p=0.07), and underestimation of EF (0.1%, p=0.92) with MDCT compared with MRI. All limits of agreement between both modalities (EF: +/-15.7%, EDV: +/-31.0 ml, ESV: +/-18.0 ml) were in a moderate but acceptable range. Interobserver variability of MDCT was not significantly different from that of MRI. For MDCT software, the post-processing time was significantly longer (19.6+/-5.8 min) than for MRI (11.8+/-2.6 min, p<0.001). Accurate assessment of right ventricular volumes by 16-detector CT is feasible but still rather time-consuming.